Versatile Click Cyanine Amino Acid Conjugates Showing One‐Atom‐Influenced Recognition of DNA/RNA Secondary Structure and Mitochondrial Localisation in Living Cells. Issue 14 (16th April 2018) - Šmidlehner, Tamara; Kurutos, Atanas; Slade, Jakov; Belužić, Robert; Ang, Dale L.; Rodger, Alison; Piantanida, Ivo
Abstract : By a simple click CuAAC (copper(I)‐catalysed azide alkyne cycloaddition) procedure several cyanine dye analogues have been attached to the side‐chain of an amino acid to yield chromophore amino acid conjugates with the potential to fluoresce upon binding to a target. Due to the availabiltiy of the amino acid C and N termini for peptide coupling, these conjugates are suitable for easy incorporation into the backbone of peptides. The novel amino acid dyes prepared in this work, although intrinsically non‐fluorescent, gave rise to strong fluorimetric responses upon binding to double‐stranded (ds) DNA or RNA, the emission response to various polynucleotide secondary structures being controlled either by linker length or a halogen atom located on the cyanine part of the molecule. Molecular modelling confirmed the mode of binding to different polynucleotides, which was responsible for the recognition. Interestingly, cell localisation experiments showed that the dyes were specifically localised in mitochondria at variance with the localisation of the parent dyes, which accumulate in cell nuclei, which suggests that the amino acid tail (containing a triazole ring) might function as a novel mitochondria‐directing appendage. Abstract : Novel amino acids incorporating cyanine dyes in side‐chain show DNA/RNA secondary structure recognition through their fluorescence and CD response, finely tuned by halogen substituents on the cyanine. Some dyes, being non‐toxic, specifically stained mitochondria in living human cells, the triazole amino acid tag behaving as a novel mitochondria‐directing moiety.